Pendampingan Penyusunan Laporan Keuangan Umkm Cv. XYZ di Kota Pekanbaru - Siti Rodiah; Yovanna Nabila Azzahra; Nur Azizah; Ilma Amelia; Olipian Resky Pernando (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Financial reporting that is easy to understand and transparent is a necessity for all types of businesses in the modern era. This cannot be separated from the fact that financial reports showing the results of a company's performance are one of the main foundations for making management decisions. A company in the form of a Commanditaire Vennootschap (CV) is one of the business units that still requires support in reporting its financial reports. This is because regulations This company and SAK-ETAP are not yet widely understood by all groups and still need to be socialized. This service is carried out using a qualitative methodology approach, namely data collection methods: interviews, observation and document analysis. Based on the results of preparing financial reports, CV. XYZ still uses manual preparation of financial reports so assistance is needed.